Vitamin D3 Regulates Follicular Development and Intrafollicular Vitamin D Biosynthesis and Signaling in the Primate Ovary - Xu, Jing; Lawson, Maralee S.; Xu, Fuhua; Du, Yongrui; Tkachenko, Olena Y.; Bishop, Cecily V.; Pejovic-Nezhat, Lucas; Seifer, David B.; Hennebold, Jon D. (Frontiers in Physiology, 2018)
There is an increasing recognition that vitamin D plays important roles in female reproduction. Recent studies demonstrated that 1α,25-dihydroxyvitamin D3 (VD3), the biologically active form of vitamin D, improved ovarian follicle survival and growth in vitro. Therefore, we investigated the direct effects of VD3 at the specific preantral and antral stages of follicular development, and tested the hypothesis that vitamin D receptor and enzymes critical for vitamin D biosynthesis are expressed in the primate ovary. Fourteen adult rhesus macaques provided ovarian tissue. Secondary and antral follicles were isolated for PCR analysis on vitamin D receptor, vitamin D3 25-hydroxylase, and 25-hydroxyvitamin D3-1α-hydroxylase. Vitamin D receptor protein localization was determined by immunohistochemistry on ovarian sections. Isolated secondary follicles were cultured under conditions of control and VD3 supplementation during the preantral or antral stage. Follicle survival, growth, steroid and anti-Müllerian hormone production, as well as oocyte maturation were evaluated. In vivo- and in vitro-developed follicles were also assessed for genes that are critical for vitamin D biosynthesis and signaling, gonadotropin signaling, steroid and paracrine factor production, and oocyte quality. The mRNA encoding vitamin D receptor, 25-hydroxylase, and 1α-hydroxylase was detectable in in vivo- and in vitro-developed preantral and antral follicles. The 25-hydroxylase was elevated in cultured follicles relative to in vivo-developed follicles, which further increased following VD3 exposure. VD3 treatment increased 1α-hydroxylase in in vitro-developed antral follicles. The absence of VD3 during culture decreased vitamin D receptor expression in in vitro-developed antral follicles, which was restored to levels comparable to those of in vivo-developed antral follicles by VD3 supplementation. Positive immunostaining for vitamin D receptor was detected in the nucleus and cytoplasm of granulosa cells and oocytes. While only survival was improved in preantral follicles treated with VD3, VD3 supplementation promoted both survival and growth of antral follicles with increased estradiol and anti-Müllerian hormone production, as well as oocyte maturation. Thus, Vitamin D biosynthesis and signaling systems are expressed in primate ovarian follicles. Our findings support a role for VD3 in regulating follicular development in a stage-dependent manner, as well as the intrafollicular vitamin D biosynthesis and signaling, directly in the ovary.